2022
DOI: 10.3390/agronomy12092047
|View full text |Cite
|
Sign up to set email alerts
|

Crop Yield and Nutrient Efficiency under Organic Manure Substitution Fertilizer in a Double Cropping System: A 6-Year Field Experiment on an Anthrosol

Abstract: The combination of organic manure and inorganic fertilizer plays a role in increasing crop yield and nutrient efficiency, but such effectiveness varies with crop, soil, management, and climate. Here, a 6−year field experiment was conducted to evaluate the effects of substituting organic manure with inorganic fertilizer on crop yield, grain protein content, and nitrogen and phosphorus efficiency under a winter wheat−summer maize cropping system on Anthrosol. Five treatments were included: recommended nitrogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Protein is an important index to evaluate wheat grain quality. The present study found that, compared with FN, the grain protein content under RN and OSN significantly decreased, which was consistent with the results of Han et al. (2022) .…”
Section: Discussionsupporting
confidence: 91%
“…Protein is an important index to evaluate wheat grain quality. The present study found that, compared with FN, the grain protein content under RN and OSN significantly decreased, which was consistent with the results of Han et al. (2022) .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the NEupk values were 0.42-1.19, which was similar to the international recommended value of 0.5-0.9 [91]. These findings were supported by Han et al [92], who highlighted that an NEupk < 1 indicates that the uptake of N is less than the input N. In this study, the N application rate of N 600 and N 720 were wasted under the annual spring wheat-summer maize cropping system.…”
Section: Discussionsupporting
confidence: 91%
“…Previous works suggested that organic fertilizers can improve the removal/absorption of N and K by wheat crops, justifying the higher protein contents in manure amended wheat grains (Hammad et al 2020; He et al 2022). Others found that reductions happened in wheat grain protein content following the replacement of inorganic fertilizer with manure (e.g., Wang et al, 2018;Han et al, 2022). These contradictory results might be explained by the variations in N supply and removal.…”
Section: Effects Of Different Treatments On Wheat Grain Proteinmentioning
confidence: 99%